2023
DOI: 10.1186/s12951-022-01758-2
|View full text |Cite
|
Sign up to set email alerts
|

A pH-responsive metal-organic framework for the co-delivery of HIF-2α siRNA and curcumin for enhanced therapy of osteoarthritis

Abstract: The occurrence of osteoarthritis (OA) is highly correlated with the reduction of joint lubrication performance, in which persistent excessive inflammation and irreversible destruction of cartilage dominate the mechanism. The inadequate response to monotherapy methods, suboptimal efficacy caused by undesirable bioavailability, short retention, and lack of stimulus-responsiveness, are few unresolved issues. Herein, we report a pH-responsive metal-organic framework (MOF), namely, MIL-101-NH2, for the co-delivery … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…19 Schematic representation of pH-responsive MOFs for osteoarthritis. 430 ery systems based on stimuli-responsive MOFs, some problems remain unsolved. There is currently a lack of systematic and comprehensive naming standard to uniformly name complex MOFs.…”
Section: Challenges and Further Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Schematic representation of pH-responsive MOFs for osteoarthritis. 430 ery systems based on stimuli-responsive MOFs, some problems remain unsolved. There is currently a lack of systematic and comprehensive naming standard to uniformly name complex MOFs.…”
Section: Challenges and Further Perspectivesmentioning
confidence: 99%
“…The in vivo results demonstrated that compared with the destruction of cartilage tissue in groups of blank control and PCA, newly formed glossy and smooth cartilage-like tissues were observed in the MOF@HA@PCA group. Zhang et al fabricated pH-responsive MIL-101-NH 2 nanoparticles loaded with curcumin (CCM) and small interfering RNA (siRNA) for hypoxia-inducible factor (HIF-2α), denoted as MCS NPs, for OA treatment 430 (Fig. 19).…”
Section: Stimuli-responsive Drug Release Based On Mofs For Various Di...mentioning
confidence: 99%
“…151 Compared with normal cartilage, the expression of hypoxia-inducible factor 2α (HIF-2α) is significantly increased in articular chondrocytes of osteoarthritis (OA) patients, which induces calcification as well as apoptosis of hypertrophic chondrocytes around the perichondral bone, leading to cartilage matrix degradation. 152 Constructing a suitable gene vector to silence the HIF2α gene in articular chondrocytes will be the key to alleviating articular cartilage degeneration and treating OA. However, articular cartilage itself has no blood vessels, nerve tissue, and lymphatic distribution, and the extracellular matrix of chondrocytes is dense (pore size of about 60 nm) and has a negative electrical barrier, making it difficult to deliver drugs/genes to chondrocytes.…”
Section: Biological Applicationmentioning
confidence: 99%
“…3C). 61 The loading of both CCM and siRNA onto MIL-101-NH 2 was accomplished through a combination of encapsulation mechanisms and the surface coordination capabilities inherent to MIL-101-NH 2 . These in vitro experiments revealed that MIL-101-NH 2 exhibits a pronounced protective effect against siRNA, shielding it from nuclease degradation via lysosomal escape.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%